2011
DOI: 10.1007/s00704-011-0565-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indian summer monsoon simulation by Community Atmosphere Model (CAM3)

Abstract: Seasonal prediction of Indian Summer Monsoon (ISM) has been attempted for the current year 2011 using Community Atmosphere Model (CAM) developed at the National Centre for Atmospheric Research (NCAR). First, 30 years of model climatology starting from 1981 to 2010 has been generated to capture the variability of ISM over the Indian region using 30 seasonal simulations. The simulated model climatology has been validated with different sets of observed climatology, and it was observed that the simulated climatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…During the analysis of model climatology, a systematic rain-bias has been observed and removed by statistical bias correction technique that is being plugged along with the model configuration (figure 1). The rain-bias correction methodology, the validation of model generated rainfall climatology along with a glimpse of seasonal rainfall forecast (without any validation) for ISM 2011 for a single ensemble CAM experiment during the June-phase were discussed in the earlier work (Das et al 2012). However, there was no scope for the detailed analysis of all seasonal forecast experiments of ISM 2011 which had been done in three experimental phases during April, May and June, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the analysis of model climatology, a systematic rain-bias has been observed and removed by statistical bias correction technique that is being plugged along with the model configuration (figure 1). The rain-bias correction methodology, the validation of model generated rainfall climatology along with a glimpse of seasonal rainfall forecast (without any validation) for ISM 2011 for a single ensemble CAM experiment during the June-phase were discussed in the earlier work (Das et al 2012). However, there was no scope for the detailed analysis of all seasonal forecast experiments of ISM 2011 which had been done in three experimental phases during April, May and June, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The present work is a continuation of Das et al (2012), with slight difference in objective. The actual performance of different phases of forecast experiments sensitive towards the different persistent SSTs when compared with observations is the main focus of the work.…”
Section: Introductionmentioning
confidence: 99%
“…IMD data are also validated against another observational dataset namely APHRODITE (Yatagai et al, ) and are found to be nearly identical (Rajeevan and Bhate, ). The IMD dataset is used in numerous works to study various observed dynamical aspects of ISM precipitation as well as a reference in evaluation of climate models (Das et al, ; Kumar et al, ; Pattnayak et al, , ; Das et al, ; Maharana and Dimri, , ). Furthermore, it is available at a resolution of 0.5° which is on the same grid as CORDEX‐SA RCMs, therefore they can be directly compared without interpolation.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the model was tested for simulating ISM rainfall, and the model climatology was generated using a long-term simulation of 30 years. During the validation of model climatology a spatial and temporal bias in the rainfall simulation was noticed, and subsequently, a bias correction methodology was developed and implemented in the model for the Indian monsoon region (DAS et al 2012). The experimental forecast system predicts the daily, monthly and seasonal rainfall for June-September over the Indian landmass region through ensemble CAM-CLM simulation in T85 (*1.41°9 1.41°) and T170 (*0.7°9 0.7°) resolution.…”
Section: Seasonal Forecast Of Ism Rainfallmentioning
confidence: 99%
“…Presently, the atmosphere-land component of the CCSM model is used (DAS et al 2011) for experimental seasonal forecast at SAC. Every year upon completion of the summer monsoon season, the experimental seasonal and 30-day forecasts have been assessed with actual observations, and shortcomings in the forecast system have been identified for improvement in the subsequent year's forecasts (DAS et al 2012(DAS et al , 2013. On completion of 5 years since 2009, it is required to quantify the overall validation of the forecast system, and to assess the scope for further improvements of these experimental seasonal forecasts over time, if any.…”
Section: Introductionmentioning
confidence: 99%